In vivo assessment of aged human skin with a unilateral NMR scanner. (21st April 2015) - Bergman, Elad; Sarda, Yifat; Ritz, Noa; Sabo, Edmond; Navon, Gil; Bergman, Reuven; Nevo, Uri
<x xml:space="preserve">Abstract</x> Human skin undergoes morphological and biochemical changes as a result of chronological aging and exposure to solar ultraviolet irradiation (photoaging). Noninvasive detection of these changes may aid in the prevention and treatment of both types of aging. This article presents a noninvasive method for the evaluation of aging skin with a unilateral stray field NMR scanner. These portable and inexpensive scanners may be suitable for in‐depth skin characterization. In vivo profiles of sun‐protected and sun‐exposed skin from the forearms of female subjects of different ages (n = 9) were measured. Skin biopsies for histopathological examination were used as reference. T2 analysis with a bi‐exponential decay model was applied and the extracted parameters were examined as markers for dermal aging. In the upper reticular dermis, a significant increase in the fraction of the slow T2 component and in the T2 value itself was found to correlate with chronological aging. For most subjects, there was an additional increase in the values of the slow T2 component and the T2 values from the sun‐exposed forearm, superimposed on that measured for the sun‐protected forearm. These results are in agreement with the decline in collagen content and the increase in free water content with aging. The results suggest that such a technique can be used as a tool for the assessment of aging, and that bi‐exponential fitting can produce sensitive fingerprint parameters for the dermal alterations that occur during aging. Copyright © 2015 John Wiley & Sons, Ltd.